G-CSF increases calprotectin expression, liver damage and neuroinflammation in a murine model of alcohol-induced ACLF - Ortega-Ribera, Martí; Zhuang, Yuan; Brezani, Veronika; Thevkar Nagesh, Prashanth; Joshi, Radhika S.; Babuta, Mrigya; Wang, Yanbo; Szabo, Gyongyi (Frontiers in Cell and Developmental Biology, 2024)
Background and aims: Granulocyte colony-stimulating factor (G-CSF) has been proposed as a therapeutic option for patients with ACLF, however clinical outcomes are controversial. We aimed at dissecting the role of G-CSF in an alcohol-induced murine model of ACLF. Methods: ACLF was triggered by a single alcohol binge (5g/Kg) in a bile duct ligation (BDL) liver fibrosis model. A subgroup of mice received two G-CSF (200 μg/Kg) or vehicle injections prior to acute decompensation with alcohol. Liver, blood and brain tissues were assessed. Results: Alcohol binge administered to BDL-fibrotic mice resulted in features of ACLF indicated by a significant increase in liver damage and systemic inflammation compared to BDL alone. G-CSF treatment in ACLF mice induced an increase in liver regeneration and neutrophil infiltration in the liver compared to vehicle-treated ACLF mice. Moreover, liver-infiltrating neutrophils in G-CSF-treated mice exhibited an activated phenotype indicated by increased expression of CXC motif chemokine receptor 2, leukotriene B4 receptor 1, and calprotectin. In the liver, G-CSF triggered increased oxidative stress, type I interferon response, extracellular matrix remodeling and inflammasome activation. Circulating IL-1β was also increased after G-CSF treatment. In the cerebellum, G-CSF increased neutrophil infiltration and S100a8/9 expression, induced microglia proliferation and reactive astrocytes, which was accompanied by oxidative stress, and inflammasome activation compared to vehicle-treated ACLF mice. Conclusions: In our novel ACLF model triggered by alcohol binge that mimics ACLF pathophysiology, neutrophil infiltration and S100a8/9 expression in the liver and brain indicate increased tissue damage, accompanied by oxidative stress and inflammasome activation after G-CSF treatment.